Comparative Study of the CSR Initiatives of Microsoft, IBM, Google, Sun Microsystems and Cisco Systems in the Gulf Region - Datta, Debarshi (2008)
The individual report of our group management project on the comparative study of the CSR initiatives of Microsoft, IBM, Google, Sun Microsystems in the Gulf Region, is my account of the entire experience of our group project, from the days of thinking about doing a management project together as a group, till the completion of the project. I have tried to illustrate all the key experiences and events that I thought to be of relevance for the group project using a narrative approach that unfolds our experience in a natural sequence of the events that occurred in the course of our project. In most parts of this report, I have used “we”, as our group, consisting of Huzaifa Sikander, Seyed Amirhossein Ghazinoori, Ravi Krishnan N and myself, Debarshi Datta, participated together in most of the activities during our project. It started from the initial planning for the project, preparing the proposal for Microsoft, reading relevant academic articles together, traveling to Dubai for the research interviews, analyzing the CSR initiatives of Microsoft and conducting a gap analysis of the CSR initiatives of our firms in the Gulf and coming up with relevant recommendations for future. I have also mentioned about my specific contributions in the group report, along with the same for Huzaifa, Amir and Ravi, as and when appropriate, in the course of narrating the entire experience of the project. I have finally concluded the report by stressing on the key factors that were the pillars behind the successful completion of our project. In this regard, I have first talked about the guidance provided by our academic supervisor, Dr. Avvari Mohan and our administrative supervisor, Dr. Thomas Thornborrow, whose suggestions and insights enriched the quality of our group project report to a large extent. Last but not the least, I have talked about our amazing group dynamics and team spirit that helped us to overcome any obstacles and challenges along our way and motivated us to perform at our very best for the project.